Internet Service Selection Decision Support System Using the Analytical Hierarchy Process (AHP) Method (Case Study of PT Media Antar Nusa) - Siregar, Nugrah Anggara; Pinem, Mhd Zulfikar; Niska, Debi Yandra (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In the digital era, the need for reliable and high-quality internet services has become critical for business operations. PT Media Antar Nusa faces the challenge of selecting the most suitable Internet Service Provider (ISP) from a wide range of options. This study aims to develop a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to assist the company in making structured and objective decisions. The research process includes identifying relevant criteria (price, speed, and connection stability), building a hierarchical structure, performing pairwise comparisons, evaluating consistency, and determining priority weights. Data were collected through literature studies, direct observation, and expert interviews. The AHP method proved effective in selecting the optimal ISP alternative, with fiber optic dedicated services achieving the highest priority scores across all criteria. The consistency ratio obtained was below the threshold of 0.1, indicating valid and consistent decision-making. The developed DSS successfully provides transparent and measurable recommendations to support PT Media Antar Nusa’s operational efficiency and strategic decision-making regarding internet service selection.